2003
DOI: 10.1016/s0741-5214(02)75336-6
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine secretion of transforming growth factor-β1 in aneurysm healing and stabilization with endovascular smooth muscle cell therapy1 1Competition of interest: none.

Abstract: Healing and stabilization of aneurysms with endovascular cell therapy is associated with a specific pattern of gene expression, resulting in paracrine secretion of TGF-beta(1). Our study provides insight into the molecular mechanisms of arterial aneurysm healing and stabilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…A previous endovascular vascular smooth muscle cell seeding experiment in rats showed that stabilization of the diameter of expanding experimental AAAs was associated with increased expression and paracrine secretion of TGF-β1 within the aorta, supporting its ability to promote healing of AAAs. 33 These reports further support our observations of the protective role of TGF-β1 in AAA pathogenesis. Leucine-serine-lysine-leucine (LSKL) peptide attenuates transforming growth factor-beta 1 (TGF-β1) activity and Smad signaling in angiotensin II (AngII)-infused ApoE −/− mice.…”
Section: Discussionsupporting
confidence: 87%
“…A previous endovascular vascular smooth muscle cell seeding experiment in rats showed that stabilization of the diameter of expanding experimental AAAs was associated with increased expression and paracrine secretion of TGF-β1 within the aorta, supporting its ability to promote healing of AAAs. 33 These reports further support our observations of the protective role of TGF-β1 in AAA pathogenesis. Leucine-serine-lysine-leucine (LSKL) peptide attenuates transforming growth factor-beta 1 (TGF-β1) activity and Smad signaling in angiotensin II (AngII)-infused ApoE −/− mice.…”
Section: Discussionsupporting
confidence: 87%
“…37 We have shown previously that endovascular seeding of VSMCs stabilized the diameter of expanding experimental AAAs, supporting the concept that correction of the quantitative VSMC defect allows functional healing of AAAs. 14,38 Accumulation of VSMCs is elicited in normal and injured vessel wall by TGF-␤1 overexpression. 20,21 In the present study, overexpression of active TGF-␤1 resulted in the development of a VSMC-rich intimal thickening, which tended to replace the luminal thrombus and likely participated in wall strengthening because of its dense collagen and elastic fiber networks.…”
Section: Reconstruction Of the Artery Wallmentioning
confidence: 99%
“…69 TGF-␤ 1 may stabilize experimental aneurysms. 70 TGF-␤ 1 also inhibits proteolysis and endothelial cell migration. 71,72 Thus, TGF-␤ 1 could be locally expressed to inhibit recanalization and favor neointima formation at the neck of treated aneurysms.…”
Section: Candidate Genes To Improve Results Of Endovascular Treatmentmentioning
confidence: 99%